1972
DOI: 10.1126/science.178.4061.623
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Lepore Trait: Globin Synthesis in Bone Marrow and Peripheral Blood

Abstract: There was decreased synthesis of the beta-globin chain in the peripheral blood, and equal synthesis of alpha- and non-alpha-chains in the bone marrow of three patients with hemoglobin Lepore trait, similar to the findings in patients with heterozygous beta-thalassemia. There is a relative instability of the synthetic mechanism for normal beta-chain in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…As expected, these patients have a pool of radioactive free a-chains in the peripheral blood larger than that found in control patients (6,7,9,13). We have previously described balanced globin chain synthesis in the bone marrow of patients with heterozygous P-thalassemia and related disorders (14)(15)(16). The gel filtration studies in this paper demonstrate the existence of a small pool of free a-chains in normal human bone marrow and a much larger pool in patients with heterozygous P-thalassemia, sickle-thalassemia, and Hb Lepore trait.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…As expected, these patients have a pool of radioactive free a-chains in the peripheral blood larger than that found in control patients (6,7,9,13). We have previously described balanced globin chain synthesis in the bone marrow of patients with heterozygous P-thalassemia and related disorders (14)(15)(16). The gel filtration studies in this paper demonstrate the existence of a small pool of free a-chains in normal human bone marrow and a much larger pool in patients with heterozygous P-thalassemia, sickle-thalassemia, and Hb Lepore trait.…”
Section: Introductionsupporting
confidence: 56%
“…METHODS Patients. The patients studied, several of whom have been described previously, included one Italian and one Iraqi with p-thalassemia trait (16), two American Negroes and one Italian with sickle p-thalassemia (16), three Italians with Hb Lepore trait (15), one Italian man doubly heterozygous for a-and 8-thalassemia (a#-thalassemia), four Italian children with homozygous p-thalassemia, and one Italian child doubly heterozygous for Hb Lepore and high Hb A2 p-thalassemia. The patients with fl-thalassemia trait had increased levels of Hb A2, hypochromia, microcytosis, and normal serum iron levels.…”
Section: Introductionmentioning
confidence: 99%
“…An apparently balanced synthesis of globin occurs at the expense of total reduction of hemoglobin synthesis, because the cells of these patients are hypochromic and microcytic (Table I). Recently, Gill, Atwater, and Schwartz have shown that a similar phenomenon exists in patients heterozygous Jfor Hb Lepore: alpha/beta globin chain synthesis is close to 1 in the bone marrow of these/ patients while unbalanced synthesis occurs in the peripheral reticulocytes even though there is very little Hb Lepore produced in either cell type (23).…”
Section: Discussionmentioning
confidence: 87%
“…In P-thalassemia, the excess a-chains are a reflection of the deficient synthesis of f-chains associated with a decreased cellular content of the messengerRNA for fglobin (8)(9)(10)(11). A similar imbalance in globin chain synthesis has been noted in heterozygotes for hemoglobin Lepore Boston (12,13). In the hemoglobin Lepore syndrome, synthesis of the 8-fl fusion chain is markedly reduced in comparison to f8-chain synthesis.…”
Section: Discussionmentioning
confidence: 82%